Expression of matrix metalloproteinase -2 in Breast cancer - Ismail, Noor H. (Iraqi Journal of Cancer and Medical Genetics, 2013)
Formalin-fixed , paraffin embedded blocks tissue for thirty one breast cancer patients were obtained from the archive of the Pathology laboratory of Al-Yarmouk Teaching Hospital from January 2011 to July 2012 . In addition Formalin-fixed , paraffin embedded blocks tissue for ten fibroadenoma of breast were collected and used as control group . These blocks were subjected to cut as serial thin sections of (4μm) thickness and were sticked on positive charge slides to be used for in situ hybridization for the detection of matrix metalloproteinase -2 in breast cancer (MMP-2) . Overexpression of MMP-2 was detected in 90.3% (28 out of 31) of breast cancer samples (> 50% of the cells appearing as positive) . The remaining 3 samples (9.7%) showed a weak- moderately expression (< 50% of the cells appearing as positive) . The statistical analysis demonstrated a highly significant differences in MMP-2 expression among patients with breast cancer when compared with fibroadenoma of breast patients (control group) . In conclusion MMP-2 plays an important role in pathpgensis of breast cancer and supports the evidence of its role in evolution , progression and cell survival of breast cancer .